Correlation of liver enzymes and haematological profile in thalassemia major patients - Jain, Chetana; Kumar Bhargav, Ajay; Pawan, Kavita (International Journal of Medical Research and Review, 2015)
Introduction: Although red cell transfusions are lifesavers for patients with thalassemia, they are responsible for a series of complications and expose the patients to a variety of risks. Thalassemia major is the most common genetic disease caused by defective gene which produces abnormal haemoglobin. Material and Methods: We have investigated 100 patients of Thalassemia coming to blood bank for regular blood transfusion. Level of hemoglobin,TLC,DLC and Liver enzymes i.e. SGOT, SGPT, Alkaline Phosphatase along with S. Bilirubin were also estimated. The age group of children suffering from Thalassemia major was between one year to fifteen years. Results: Serum Ferritin Level was 2251 + 315 ng/ml(mean+S.D ), Haemoglobin level was 7.82 + 0.83 gm/dl,TLC was 7200 + 1000 cells/cmm, DLC was 68 + 12 Neutrophils,29 + 08 Lymphocytes,02 + 01 Eosinophils,01 + 00Monocytes,00 + 0.1 Basophils, SGOT (AST) value was 117 + 35.5 IU/L and SGPT(ALT) concentration 151 + 47.2 IU/L and Alkaline Phosphatase level was found to be 288 + 20.80 IU/L with mean + S.D. Bilirubin was 2.55 +1.12 mg/dl (mean + S.D). Conclusion: In Present study Liver Enzymes increased and haemoglobin level was reduced but no changes were found in TLC and DLC.